Variation in physiological parameters of some ber (Ziziphus maurtiana var. rotundifolia) cultivars (Indian Journal of Arid Horticulture, 2025)
The gene pool of the ber (Ziziphus maurtiana) cultivars available in the National repository at Central Institute for Arid Horticulture, Bikaner was evaluated for the variation in the photosynthetic rate and associated parameters. It was observed that the ber cultivars showed a marked variation on the basis of photosynthetic rate and can be grouped into two groups viz i) showing mid day depression and ii) those which do not show mid day depression. The results on relative water content of leaves demonstrated that leaves of group (i) maintains high RWC as compared to that in group (ii)
Keywords: Ber (Ziziphus maurtiana); photosynthetic rate; mid day depression